PENGARUH EKSTRAK KULIT PISANG AMBON (Musa paradisiaca var. sapientum (L.) Kunt) DAN EKSTRAK TAUGE (Flammulina velutipes) PADA KERAGAAN PLANLET KENTANG GRANOLA (Solanum tuberosum L.) PADA KULTUR IN VITRO - Aini Fitri; Diky Setya Diningrat (KENANGA : Journal of Biological Sciences and Applied Biology, 2024)
This study aims to determine the effect of Ambon banana peel extract (Musa Paradisiaca var. sapientum (L.) Kunt) and bean sprout extract (Flammulina velutipes) on the growth of granola potato (Solanum tuberosum L.) in vitro. This research was conducted in July-September 2023 at the G10 Agro Tech Medan tissue culture laboratory. In this study, potato plants were grown on Murashige and Skoog (MS) media combined with Ambon banana peel extract and bean sprout extract, using a completely randomized design (CRD) research design, with four treatments and three replicates with a concentration consisting of 4 levels, namely Ambon banana peel extract 0 g/l, 20 g/l, 40 g/l and 60 g/l and bean sprout extract, namely 0 g/l, 20 g/l, 40 g/l and 60 g/l. The observation parameters in this study were the number of roots, number of shoots, number of leaves and plant height. The data obtained were analyzed using Analysis of variance (ANOVA) and on different treatments, Duncan's multiple range test (DMRT) was conducted. The results of the analysis after the 4th observation week after planting (WAP) showed that the treatment of the addition of Ambon banana peel extract and bean sprouts had a significant effect on the number of roots, number of shoots, number of leaves and plant height. The best number of roots was produced by the combination of KP60T40 (60 g/l Ambon banana peel extract + 40 g/l bean sprouts extract) which was 10 root fibers. The number of shoots produced by KP60T20 (60 g/l Ambon banana peel extract + 20 g/l bean sprout extract) is 15.67 shoots. The highest number of leaves is KP20T20 (Ambon banana peel extract 20 g/l + bean sprout extract 20 g/l) which is 14 leaves and the treatment combination on plant height is produced by KP20T60 which is 13.67 cm. So it can be concluded that organic media of Ambon banana peel and bean sprouts can be used as alternative media because it gives a real influence on the growth of granola potatoes in vitro.